Crystal Growth and Manipulation of Intercalated Chalcogenides as Superconductors and Topological Insulators - (:unkn) unknown (My University, 2018)
Superconductors are unusual quantum materials which offer no resistance to electric current. The fascinating physics of this phenomenon is complemented by wide-ranging technical applications from power transmission to magnetic levitation. Commercially successful superconductors are found in powerful magnets in medical imaging, particle accelerators, and next-generation quantum computing. In my effort to uncover the mysteries and fundamental mechanisms of superconductivity, I use an array of techniques to synthesize and study single crystals of unconventional superconductors including the iron telluride and bismuth selenide family of superconductors. My study of atomic valence and crystal structure in iron telluride has uncovered previously unknown chemical and structural dependencies of the superconducting state. Taken together, there exists a much stronger dependence than previously known on how elemental concentration, structural defects, and atomic valence determine material properties. In addition, the development of methods to produce high-quality single crystals has enabled my study and modeling of the electronic structure of bismuth selenide at high magnetic fields, previously impossible with lower quality materials. In bismuth selenide, my results show superconductivity is achieved only in samples quenched above 560 °C, with samples quenched at 620 °C showing superconductivity correlated with an expanded Fermi surface cross-section, increase in Fermi energy, and appearance of nematic charge density waves. Oxygen treatments known to induce superconductivity in thin film iron telluride were applied to bulk iron telluride and found to cause the valence states of tellurium and iron to shift from Te0 and Fe2+ to Te4+ and Fe3+¸ consistent with oxygen bonding to tellurium and the formation of Fe2O3. Additionally, oxygen causes the formation of an oriented FeTe2 intergrowth in single crystals, and the formation of a spin glass magnetic state stable up to room temperature.
Keywords: Chalcogenide; Intercalation; Superconductor; Topological insulator